Penyuluhan Tentang Cara Pencegahan Penularan TB dan Pemakaian Masker Kepada Keluarga Penderita TB di Johar Baru, Jakarta Pusat - Kholis Ernawati; Rifqatussa’adah Rifqatussa’adah; Rifda Wulansari; Ndaru Andri Damayanti; Titiek Djannatun (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Health education on transmission prevention and use of masks in families with tuberculosis patient: the experience from Johar Baru, Central JakartaPurposeThe objective of the activity is to educate TB patients and families of TB patients about how to prevent TB transmission and the correct use of masks and the use of masks.MethodActivity targets were 35 people from 20 families of TB patients in Johar Baru area, Central Jakarta. Activities carried out were socialization, counseling about the use of masks, giving masks to respondents, and evaluation activities. The extension media used were posters on